The penalty resulting from the breach of the legal expert's obligations under Jordanian law - Al-Aqrabawi, Esam Hasan (Journal of Economic, Administrative and Legal Sciences, 2019)
This paper deals with the subject of the penalty resulting from the violation of the obligations of the legal expert in accordance with Jordanian law, it is known that many of the courts of different types and degrees draw in many of the lawsuits the opinion of the people of experience and study on certain issues, or cannot prevent the judge deciding which of its own.Because for his judicial expert of the work is directly related to individuals of society and liberties and rights, which requires him a lot of time and accuracy in achievement, and as the nature of his work related to justice, there must be controls allow opponents of his claim for compensation whenever their right to harm illegal according to the principles Civil responsibility.So the study came to discuss the penalty resulting from the breach of the expert legal obligations for damages that may be caused to opponents and my study was divided through a preliminary study, and two.In the introductory section, it dealt with the civil liability of the judicial expert from the act, damage and causal relationship between the act and the injury. And proving the civil liability of the judicial expert in the first subject.The second part dealt with the effects of the responsibility of the judicial expert in the suits of compensation. This section was divided into two requirements, which dealt with the first requirement of compensation and the judge's discretion, and the second demand on how to compensate the expert's damages.
Keywords: judicial expert; civil law; Jordan; civil liability